Synthesis and Characterization of a New Complexo Cobalt (III) Sulfasalazine Hydroxamate - Ghashim, Lamia Lafta (Al-Nahrain Journal of Science, 2018)
Cobalt () Sulfasalazine hydroxamate complex was synthesized and characterized by physicochemical and spectroscopic methods. A spectroscopic investigation of its reaction with Co() revealed the sole formation of the 1:3 complex at equilibrium. The isolated complex indicated octahedral coordination via the (N) atom of the hydroxamate group. The limiting concentration for interference by Ni(), Cd(), AI(), and Zn() cations were reported. Microbial sensitivity test on five microorganisms were tested.